2014
DOI: 10.1007/s10549-014-2918-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between cadmium and breast cancer risk according to estrogen receptor and human epidermal growth factor receptor 2: epidemiological evidence

Abstract: The study aimed to examine the association between cadmium (Cd) and the risk of breast cancer according to estrogen receptor (ER) and human epidermal growth factor receptor 2 (HER2). A hospital-based case-control study was carried out in 585 cases and 1,170 controls. Information on possible risk factors was collected via a structured questionnaire. Urinary Cd was determined by atomic absorption spectrometry. The ER and HER2 levels in tumor tissue were analyzed by immunohistochemistry. Logistic regression was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 23 publications
0
24
2
1
Order By: Relevance
“…Higher cadmium concentrations were reported in breast tissue from breast cancer patients than from normal breast tissue. 19,20 Some epidemiologic studies have observed increased risk of overall breast cancer among women with higher urinary cadmium levels, 3,21-23 while one reported no association for dietary cadmium intake. 24 Several studies have reported elevated risks associated with cadmium that were confined to only ER+ tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher cadmium concentrations were reported in breast tissue from breast cancer patients than from normal breast tissue. 19,20 Some epidemiologic studies have observed increased risk of overall breast cancer among women with higher urinary cadmium levels, 3,21-23 while one reported no association for dietary cadmium intake. 24 Several studies have reported elevated risks associated with cadmium that were confined to only ER+ tumors.…”
Section: Discussionmentioning
confidence: 99%
“…24 Several studies have reported elevated risks associated with cadmium that were confined to only ER+ tumors. 21,25 Julin et al, 4 however, reported increased risk for all breast cancer, ER+ tumors and ER- tumors associated with higher dietary cadmium exposure, though the ER- association was based on small numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have shown that a high urinary cadmium level was associated with an increased risk of breast cancer (McElroy et al, 2006;Gallagher et al,2010;Nagata et al, 2013;Strumylaite et al, 2014;Wei et al, 2015). A recent meta-analysis of eight epidemiological studies reported a 1.66-fold risk increase (95% confidence interval 1.50, 3.34) for each 0.5 μg/g creatinine increase in the cadmium level, although large prospective studies are still needed for confirmation (Larsson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Human exposure to Cd in the general population occurs primarily through consumption of contaminated food, although an additional source can be cigarette smoke (2012b). Cd is a human lung carcinogen and is possibly carcinogenic in the kidney, prostate, and breast (2012b; Strumylaite et al , 2014). Human exposure to environmental iAs occurs primarily by consumption of contaminated water (2012a).…”
Section: Introductionmentioning
confidence: 99%